A Comparative Study of Fintech Ecosystems in Indonesia and The Uk: A Comparative Study for Optimal Growth and Regulation - Suhardi, Agatha Rinta; Ichsani, Sakina (Applied Business and Administration Journal, 2025)
Monetary policy plays a central role in regulating a country's economic stability. Through instruments such as interest rates and cash regulations, central banks strive to control inflation, manage economic growth, and maintain financial system stability. Effective monetary policy is key to creating a stable and sustainable economic climate. This study aims to compare the fintech ecosystems in Indonesia and the UK and provide policy recommendations. Using a comparative descriptive method with analysis of literature, reports, and relevant resources, the UK is shown to have a strong financial infrastructure, progressive regulations, higher financial inclusion, and sound financial literacy. On the other hand, Indonesia faces challenges in financial infrastructure that need to be strengthened, regulations that need to be adapted, and financial access and inclusion that need to be improved. Policy recommendations include inclusive regulation through the establishment of a regulatory sandbox, collaboration between government, industry, and traditional financial institutions, increasing financial literacy through educational programs, strict data protection and cybersecurity, and improving technological infrastructure for equal access to fintech. By implementing these recommendations, Indonesia can develop an inclusive and sustainable fintech sector in line with the UK's success.